2014
DOI: 10.1242/jcs.155879
|View full text |Cite
|
Sign up to set email alerts
|

Differential binding to the ILK complex determines kindlin isoform adhesion localization and integrin activation

Abstract: BSTRACTKindlins are essential FERM-domain-containing focal adhesion (FA) proteins required for proper integrin activation and signaling. Despite the widely accepted importance of each of the three mammalian kindlins in cell adhesion, the molecular basis for their function has yet to be fully elucidated, and the functional differences between isoforms have generally not been examined. Here, we report functional differences between kindlin-2 and -3 (also known as FERMT2 and FERMT3, respectively); GFP-tagged kind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
93
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(103 citation statements)
references
References 65 publications
8
93
2
Order By: Relevance
“…Single-particle tracking studies using the mys b58 (V409D) mutation in S2 cells further support our findings (Mainali and Smith, 2013). In accordance with recent studies on mammalian ILK (Huet-Calderwood et al, 2014;Ye et al, 2013), we cannot exclude the possibility that the reduced integrin immobile fraction at the PM compromises the sustainability of integrin clustering (Welf et al, 2012).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Single-particle tracking studies using the mys b58 (V409D) mutation in S2 cells further support our findings (Mainali and Smith, 2013). In accordance with recent studies on mammalian ILK (Huet-Calderwood et al, 2014;Ye et al, 2013), we cannot exclude the possibility that the reduced integrin immobile fraction at the PM compromises the sustainability of integrin clustering (Welf et al, 2012).…”
Section: Discussionsupporting
confidence: 85%
“…In mammalian cells, IPP complex modulates integrin extracellular adhesion for ECM ligands in a talin-or kindlindependent manner (Honda et al, 2009(Honda et al, , 2013Huet-Calderwood et al, 2014). In Drosophila, talin strengthens integrin adhesion by facilitating integrin clustering rather than increasing integrin affinity (Brown et al, 2002;Bunch, 2010;Ellis et al, 2014;Helsten et al, 2008).…”
Section: Distinct Requirements Of Ipp Complex and Talin In Integrin-mmentioning
confidence: 99%
“…A study in C. elegans proposed that binding of ILK to kindlin induced a conformational change of kindlin that promotes its binding to integrin tails (Qadota et al, 2012). This mechanism, however, has not been observed with mammalian kindlin orthologues (Huet-Calderwood et al, 2014;Fukuda et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to talin, kindlins contain no obvious actin-binding sites; therefore, linkage to actin is mediated through their binding to the ILK-PINCH-parvin (IPP) complex and/or migfilin (also known as FBLIM1) (Mackinnon et al, 2002;Tu et al, 2003). Whereas the migfilin-binding site remains unknown, the ILK-binding site has been mapped to a short leucinerich, amphipathic α-helix between the F2 and PH domain of mammalian kindlins (Huet-Calderwood et al, 2014;Fukuda et al, 2014). The differential binding of kindlins to β-integrin tails is discussed in Box 1 and the binding sites for kindlin-interacting proteins are shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that these KBPs are involved in regulating integrin-mediated cell adhesion and spreading (outside-in signaling), but not integrin activation (insideout signaling). ILK has even been identified as an integrin activator (Honda et al, 2009) and can also interact with kindlin-2 (Fukuda et al, 2014;Huet-Calderwood et al, 2014); however, it has no additional effect on integrin activation mediated by TH and kindlin-2 (Fukuda et al, 2014), indicating that ILK may not fit the category of bridging molecules. Interestingly, a recent study has disclosed that ADAP, a hematopoietic-specific adapter protein, can associate with both talin and kindlin-3 and promote integrin αIIbβ3 activation in platelets (Kasirer-Friede et al, 2014), which endorses the proposed bridging molecule model.…”
Section: Introductionmentioning
confidence: 99%